Obesity, cytokines and psychopathology in patients with chronic schizophrenia - Menghan Lv; Xuan Wang; Xiayue He; Zhiren Wang; Xiaohong Li; Yunlong Tan; Xiang Yang Zhang (Frontiers in Psychiatry, 2025)
BackgroundObesity and dysregulated cytokine levels are prevalent in schizophrenia patients undergoing antipsychotic treatment. While cytokines are implicated in obesity, their relationship with psychopathology in schizophrenia remains underexplored. This study investigated associations between body mass index (BMI), cytokine levels, and clinical symptoms in chronic schizophrenia patients.MethodsIn this cross-sectional study,201chronic schizophrenia patients (Chinese Han population) were stratified into high BMI (BMI≥25kg/m2) and low BMI (BMI<25kg/m2) groups. Psychopathology was assessed using the Positive and negative Syndrome Scale (PANSS). Serum cytokine (IL-2, IL-6, TNF-α) and metabolic parameters were measured in 69 participants.ResultsA significant negative correlation was observed between BMI and IL-2(p=0.013). TNF-α levels inversely correlated with PANSS total (p=0.010) and general psychopathology scores(p=0.042). The high BMI group exhibited lower PANSS negative subscores and elevated glucose, triglycerides (TG) and apolipoprotein B (ApoB) compared to the low BMI group(all p<0.05). Multivariate regression identified IL-2 as an independent factor associated with lower BMI, while TNF-α independently contributed to general psychopathology.ConclusionsHigher BMI in chronic schizophrenia is associated with reduced IL-2 levels, attenuated negative symptoms, and adverse lipid profiles. TNF-α may modulate psychopathology severity. These findings highlight complex interactions between metabolic dysregulation, immune markers, and clinical manifestations in schizophrenia.